Development of nuclear and plastid SNP markers for genetic studies of Dipteryx tree species in Amazonia - Honorio Coronado, Euridice N.; Blanc-Jolivet, Celine; Mader, Malte; Garcia-Davila, Carmen R.; Sebbenn, Alexandre M.; Meyer-Sand, Barbara R. V. [UNESP]; Paredes-Villanueva, Kathelyn; Tysklind, Niklas; Troispoux, Valerie; Massot, Marie; Degen, Bernd (Springer, 2019)
We developed nuclear and plastid single nucleotide polymorphism (SNP) and insertion/deletion (INDEL) markers for Dipteryx species using a combination of restriction associated DNA sequencing (RADSeq) and low coverage MiSeq genome sequencing. Of the total 315 loci genotyped using a MassARRAY platform, 292 loci were variable and polymorphic among the 73 sampled individuals from French Guiana, Brasil, Peru, and Bolivia. A final set of 56 nuclear SNPs, 26 chloroplast SNPs, 2 chloroplast INDELs, and 32 mitochondrial SNPs identifying significant population structure was developed. This set of loci will be useful for studies on population genetics of Dipteryx species in Amazonia.
Keywords: Cumaru; Timber species; SNP; MassARRAY